Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3389/fimmu.2021.751772
|View full text |Cite
|
Sign up to set email alerts
|

Immunoregulation by Artemisinin and Its Derivatives: A New Role for Old Antimalarial Drugs

Abstract: Artemisinin and its derivatives (ARTs) are known as conventional antimalarial drugs with clinical safety and efficacy. Youyou Tu was awarded a Nobel Prize in Physiology and Medicine due to her discovery of artemisinin and its therapeutic effects on malaria. Apart from antimalarial effects, mounting evidence has demonstrated that ARTs exert therapeutic effects on inflammation and autoimmune disorders because of their anti-inflammatory and immunoregulatory properties. In this aspect, tremendous progress has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 78 publications
(92 reference statements)
1
9
0
Order By: Relevance
“…Previous reports showed that ART could induce tumor cell apoptosis and ferroptosis by ferrous iron-dependent ROS-triggered ER stress [45]. In addition, ART promotes the tumor cytotoxicity of T, γδT, and NK cells but lowers Treg and MDSC frequencies in tumor-bearing mice [37,46]. In our study, ART treatment decreases MDSC accumulation through DR5induced apoptosis in MDSCs.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Previous reports showed that ART could induce tumor cell apoptosis and ferroptosis by ferrous iron-dependent ROS-triggered ER stress [45]. In addition, ART promotes the tumor cytotoxicity of T, γδT, and NK cells but lowers Treg and MDSC frequencies in tumor-bearing mice [37,46]. In our study, ART treatment decreases MDSC accumulation through DR5induced apoptosis in MDSCs.…”
Section: Discussionsupporting
confidence: 69%
“…Recent reports showed that ARTs also have antitumor and immunomodulatory effects, which indicates the potential option for cancer treatment [37]. ART could reduce MDSC levels and enhance the antitumor immune response in 4T1 breast tumor model in vitro and in vivo [38].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of action of artemisinin is pluri-factorial. It implicates a carbon radical and heme, but also interaction and interference with plasmodial proteins such as the sarcoplasmic endoplasmic calcium ATPase (SERCA), as well as an induced immunoregulation [ 124 , 125 , 126 ]. A similar complexity can be anticipated with yingzhaosu A.…”
Section: Mechanism Of Action Of Yingzhaosu Amentioning
confidence: 99%
“…Several semi-synthetic derivative drugs have been obtained from ART: artemether, artemisone, artesunate (AS), artefenomel (OZ439) and artenimol or dihydroartemisinin (i.e., the active metabolite of ART). These drugs have been widely repurposed to treat several diseases including viral infections [ 121 , 122 , 123 ].…”
Section: Antimalarial Drugsmentioning
confidence: 99%